Insecticide resistance in Colombia and Ecuador (2005)
Farmer interviews conducted as part of extensive on-farm surveys for the diagnostic phase of the Tropical Whitefly Integrated Pest Management (TWF-IPM) Project (Rodríguez and Cardona, 2001; Chapter 4.1, this volume) showed that insecticide use against whiteflies in Colombia and Ecuador is excessive. In the tropical highlands and mid-altitude valleys, farmers spray their crops 5 to 6 times on average to control Trialeurodes vaporariorum (Westwood). The mean number of applications against the B biotype of Bemisia tabaci (Gennadius) in the tropical lowlands of Colombia and Ecuador was estimated at 6.5. Over-reliance on insecticides for whitefly control is so widespread that 30% of 325 farmers interviewed reported that they make more than 10 applications per cropping season. The frequency of applications in many cases is as high as two to three times per week. Most farmers complained about the limited control achieved by conventional insecticides and many farmers are now using novel insecticides such as buprofezin, pyriproxyfen, diafenthiuron and imidacloprid reportedly with better results. However, the 10 most widely used insecticides identified in the surveys comprised nine conventional products—dimethoate, carbofuran, chlorpyriphos, methamidophos, methomyl, profenofos, monocrotophos, cypermethrin and malathion—and only one of these novel insecticides, imidacloprid. The high toxicity of several of the conventional products in widespread use raises concerns over both human and environmental health, underlining the need for alternative approaches based on IPM